An overview of Takayasu Arteritis at an academic hospital in Central South Africa - Botha, Eugenie (University of the Free State, 2023)
𝗣𝘂𝗿𝗽𝗼𝘀𝗲 𝗼𝗳 𝘁𝗵𝗲 𝘀𝘁𝘂𝗱𝘆: Takayasu arteritis (TA) is a chronic granulomatous inflammatory vasculitis of large and medium vessels of unknown aetiology. It has a predilection for the aorta and its branches, and can affect the brachiocephalic, carotid, subclavian, vertebral, and renal arteries, as well as the coronary and pulmonary arteries. Expression of the disease is variable, often leading to symptoms of ischaemia due to blood vessel stenosis or thrombus formation within a vessel. An unknown, yet identified antigen, is thought to initiate an autoimmunological response in a genetically susceptible patient, where mononuclear infiltration in the vasa media leads to granulomatous inflammation resulting in medial thickening, intimal proliferation and obliteration of elastic layers and medial smooth muscles with cellular infiltration around the vasa vasorum. Disease progression causes tunica media destruction, often with resultant aneurismal formation or acute aneurismal dissection of affected arteries. The epidemiological distribution of TA is worldwide with the highest prevalence occurring in the Asian population. The disease is more prevalent in younger females with a female to male ratio of 4-9: 1. TA may show heterogeneous disease expression, patterns of arterial involvement and prognosis in different parts of the world. Available data on the African continent and specifically South Africa is limited. The largest study on adults with TA in SA was done in the Western Cape Province at Groote Schuur Hospital. Case reports have been documented in South Africa and Africa. Published literature in South Africa mainly has been focused on TA in the paediatric population group, and, in the Free State Province of South Africa, no published literature has been found. Clinical manifestations are variable, ranging from initially asymptomatic to vague and non-specific symptoms. As the disease progresses, classical features of TA begin to emerge with ischemic symptoms being a prominent feature. The classification of TA requires at least three of the six criteria of the American College of Rheumatology of 1990 to be present. There is often a delay in the diagnosis due to non-specific symptoms and variable clinical presentation. The diagnosis is often missed due to low clinical awareness and suspicion. No standardized criteria to assess disease activity have been formalized, further contributing to the difficulty in managing the disease. Thus far, no definitive biomarker has been found to diagnose TA. Imaging is paramount to making the diagnosis, establishing the extent of arterial involvement, and assessing disease progression and response to treatment. Computerised tomography angiography (CTA) or magnetic resonance angiography (MRA) is used to establish the diagnosis of TA. CTA is most often used in our setting due to restrictions to the accessibility of MRI. CTA and MRA are beneficial for the assessing the aorta and its main branches. Treatment for TA can be subdivided into medical and surgical treatment. The ultimate goal of treatment is to suppress the vascular inflammatory process. The natural history and prognosis of TA remains poorly defined. This is due to lacking data for long term follow up. Prognosis mainly depends on the development of complications, albeit from the disease itself or as a consequence of medical or surgical treatment. Further important prognostic factors are duration and extent of both vascular and systemic inflammation, late presentation and diagnosis and treatment resistance. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: Patients who met the 1990 American College of Rheumatology criteria for the diagnosis of TA were included in this retrospective study over a twenty-one-year study period from 2000 until 2021. This study comprised of adult and paediatric patients seen at Universitas Academic Hospital, in the city of Bloemfontein, Free State. They were referred to Universitas Academic Hospital, which is a tertiary institution, from other centrally located hospital in South Africa. The records of patients were reviewed, and data were analysed from the departments Rheumatology, Vascular Surgery and Paediatrics. This included patient demographics (sex, age, and ethnicity), 1990 ACR criteria, clinical features, anatomical classification, surgical interventions, medical treatment, response to therapy, complications, and outcome. Patients were excluded if there were missing data on clinical features, if no imaging studies were performed and if they had an alternate diagnosis. 𝗞𝗲𝘆 𝗿𝗲𝘀𝘂𝗹𝘁𝘀: The mean age at presentation was fourteen years (9-23), with 71.8% (n= 28) female patients, and this correlates with previous studies on sex predominance and age characteristics. The cohort constituted of 71.8% (n=28) patients of Black African ethnicity and 28.2% (n=11) patients of coloured ethnicity. There were no patients of white, Indian, or Asian ethnicities included. The most common clinical features at presentation were cardiac disease (61.5%, n=24), hypertension (56.4%, n=22) and cerebrovascular disease (48.7%, n=19). 17.9% (n=7) and 15.8% (n=6) of patients presented with peripheral vascular disease and constitutional symptoms, respectively. Gastrointestinal, respiratory, and dermatological manifestations were only present in 5.1% (n=2), respectively. Angiography demonstrated the abdominal aorta to be the most frequently involvement (71.8%, 28/39), followed by common carotid artery lesions (58.9%, 23/39), subclavian artery lesions (56.4%, 22/39) and thoracic aorta lesions (48.7%, 19/39). Therefore, Numano type IV was most commonly found in this study followed by Numano type I and type IIa. Type III and Type IIb was the least common. Stenotic lesions were more common than aneurysmal disease. 94.7% (n=36) of patients were treated with glucocorticoids (GCs). 68.4% (n=26) were combined with Methotrexate and 23.7% (n=9) with Azathioprine. 31,6% (n=12) received Cyclophosphamide 2.6% (n=1) were treated with Mycophenolate Mofetil (MMF). No patients were treated with biologics. Surgical interventions comprised mainly of open surgical procedures. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻𝘀: This study revealed that TA, which is a large vessel vasculitis, remains rare, and improving awareness is important for making an early diagnosis and preventing morbidity and mortality. The aetiology remains uncertain although an autoimmune process is implicated. Demographical data and clinical features remain comparable to previous studies worldwide and in previously done South African studies. Cardiovascular and cerebrovascular manifestations were the most frequently seen and lead to significant morbidity. Immunosuppression remains the mainstay of treatment with all patients on glucocorticoids during the course of treatment. Glucocorticoids were still heavily relied upon in the treatment of these patients. 𝗥𝗲𝗰𝗼𝗺𝗺𝗲𝗻𝗱𝗮𝘁𝗶𝗼𝗻𝘀: Future studies can be done to focus on ways in identifying patients with Takayasu arteritis earlier and exploring to identify novel biomarkers for use in diagnosis and disease activity assessment. Future research on individuals who were treated with biologics earlier in the course of their disease will be crucial to making improvements in the management of this difficult disease and comparing their outcome with patients on conventional disease modifying agents.
Dissertation(M.Med.(Internal Medicine)--University of Free State, 2023
Keywords: Takayasu arteritis; Vasculitis; Granulomatous inflammation; Young female; Clinical and radiographic findings